Preliminary of Precipitated Silica Plant from Sulphuric Acid and Sodium Silicate with Capacity of 40,000 ton/years - YUSOH, ISMAAE; , Dr. Achmad M. Fuadi, M.T; , Kun Harismah, Ph.D (2015)
In Indonesia, precipitated silica plant is an industry that can provide a good opportunity for the country. Indonesia has not been able to meet the needs of precipitated silica, so that Indonesia imports from other countries. From 2005 to 2012 Indonesia has exported 89,801.806 tons of precipitated silica, and the capacity for imports are 111,362.3 tons, so the precipitated silica plant is designing of 40,000 tons/year. Precipitated silica (SiO2) is the oxidation of non-metallic compounds. it has a solid powder form, white, odorless, insoluble in water, and has a crystalline structure. The process of manufacturing of precipitated silica using silicate acidification uses CSTR reactor (continuous stirrer tank reactor). It operates at a temperature of 90°C and at a pressure of 1 atm. This reactor proceeds in the liquid phase, irreversible, and non-adiabatic. The product of the reactor are separated in rotary vacuum filter, and then the result is a cake of SiO2. It is dried with dryer. Utility units of the plant consists of the units of the water provider, the unit of steam supply, electricity and fuel supply unit, and laboratories to maintain the quality of materials and products to conform to the standards. This company is a Limited Incorporation with a system of organizational structure and staff. As a plan, the company is built in Karawang, District Ciampel, and West Java Province. The establishment of the plant requires a total investment (capital investment) amounting to Rp 274,988,392,478.30 and production costs Rp 182,861,209,437.49. Economic analysis obtained BEP 54.8%, SDP 30.6%, 24.31% ROI before tax, ROI after tax (Inc, Ltd) 14.59%. Profit after tax earned Rp 28,550,485,320